2023
DOI: 10.3390/su151310159
|View full text |Cite
|
Sign up to set email alerts
|

Double-Edged Sword Effect of Flexible Work Arrangements on Employee Innovation Performance: From the Demands–Resources–Individual Effects Perspective

Abstract: This study explores the double-edged sword effect of FWAs on employee innovation performance based on the Demand–Resource–Individual Effect (DRIVE) model. A total of 411 valid questionnaires from knowledge-based employees were collected in three stages through a survey of technology-based companies in China. The data were analyzed using SPSS 25.0 and AMOS 22 software, and multi-level linear model analysis was conducted to test the double mediating effect of psychological empowerment and role ambiguity and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 123 publications
1
1
0
Order By: Relevance
“…Referring to the case study, whose results are in general agreement with the other international findings, as already underlined, it is possible to give a first energy increment coefficient, k x , which provides the increment of energy consumption due to remote working days, proportional to that defined in (1). It is worth mentioning that the k value is not affected by the conversion coefficients f j , because it is the angular coefficient of the consumption trend, which does not depend upon the energy source.…”
Section: Stepsupporting
confidence: 83%
See 1 more Smart Citation
“…Referring to the case study, whose results are in general agreement with the other international findings, as already underlined, it is possible to give a first energy increment coefficient, k x , which provides the increment of energy consumption due to remote working days, proportional to that defined in (1). It is worth mentioning that the k value is not affected by the conversion coefficients f j , because it is the angular coefficient of the consumption trend, which does not depend upon the energy source.…”
Section: Stepsupporting
confidence: 83%
“…In the last two decades, flexible working practices have been developed and employed to address some traditional working approach issues. The revolutionary aim of such an approach, which deconstructs the traditional working mode strictly defined in place, time, and pyramidal structures, is to achieve a "win-win" condition for both employers and employees, providing benefits for both categories [1].…”
Section: Introductionmentioning
confidence: 99%
“…The study suggests that organisations should include other supporting practices and foster an agile work culture to foster member engagement with the organisation (Weideman & Hofmeyr, 2020). Apart from that, other research found that FWA systems have a 'dark side', one of which is that remote communication tends to cause emotional exhaustion, leading to decreased work engagement (Sardeshmukh et al, 2012;Wang & Xie, 2023).…”
Section: Discussionmentioning
confidence: 97%
“…This approach recognizes the evolving needs and preferences of employees, aiming to create a more adaptable and inclusive work environment. These arrangements include remote work opportunities, flextime and flexible schedules, compressed workweeks, work-life balance and job sharing, part-time and reduced hours, and hybrid work models Wang & Xie, 2023). Some studies insist on technology integration to adopt frexible work arrangements since advanced communication and collaboration technologies is crucial for the success of flexible work arrangements (Soga et al, 2022).…”
Section: Adoption Of Flexible Work Arrangementsmentioning
confidence: 99%